Separação entre religião e Estado no Brasil: utopia constitucional? - Souza, Josias Jacintho de (2009)
The aim of this work is to analyze the historical and contemporary relationship between Religion, Law and State and the problems due to that relationship: temporary or permanent problems? If in the past the purpose of the union between Religion and State was to bring peace among people, and in modern times it s spoken about total separation also to bring peace, which is then the ideal form of relationship between Religion and State: united or separate? The theory-ideology of the union or separation between Religion and State would be a utopia? What s the importance of Law in that relationship? This research brings a proposal of terminological adaptation of the current polarity, Religious State or Lay State, by another terminology: Plural State. With the current need to think and rethink the relationship between political and religious power, the hypothesis of a Plural State represents as much the maintenance as the globalization of the cultural, political and religious diversities. A Plural State contemplates everything and everybody; as much the globalized as the regionalized State; as much the religious as the lay State. It also contemplates those who believe and disbelieve in the humanity's future divine restoration, preached by religions. Aristotle affirmed that the human being is naturally a political animal. Just political? The human being is naturally also a believing animal, not necessarily or only in the doctrines and dogmas of the religions, but in the discovered and hidden mysteries of life, in their mysteries with rational and irrational answers. During the life, everybody influences and is influenced by habits, concepts and cultural and religious truths. Therefore, trying to unite or juridically separate all cultural and religious diversities is utopia. In spite of that, the fair Law is the only means able to reasonably balance the relationships between Religion and State. There s no other way. If the ideal of a perfect society in the earth is humanly impossible, the Christianity assures that what is impossible for the men is possible for God. Thus, only He could give answers for all of the human inquiries and provide solutions for all the problems of the world. Therefore, it s only with the destruction of the utopia of the human ideals and with the effectiveness of the ideals preached by the religions that the world would be transformed. When? There s no predetermined time by the religions and neither by the planners of the utopian ideals. The utopia is similar to the horizon. When we walk towards it, it moves away from us. When we keep walking, it moves away more than before. The utopia is like this: we will never reach it. And if it s so, what s it for? To make us walk. Even being utopia the ideas and the ideals of the union or separation between Religion and State, it makes us think in a new ideal: adaptation of the historical and neomodern reality of Religious State and Lay State to Plural State. One more utopia? The utopia makes us walk. As much the political as the religious life produce ideas and ideals, united or separately: the political life intends to produce new happy life in the earth; the religious life intends to produce new happy life begun in the earth and perpetuated in the beyond, in heaven, where there s justice . Utopian ideas and or ideals as much of the political life as of the religious life? The utopia makes us walk